Analysis of the Implementation of Asset Management in the Management of State Booty - Norce Martauli Sitanggang; Dwi Setiawan (Budapest International Research and Critics University, 2022)
The management of state booty has been a long-standing problem in Indonesia. The state booty is expected to provide benefits, but due to poor management, the value decreases when the sale/auction is carried out. In addition, the cost of storage, facilities, and infrastructure and the cost of maintaining the state booty is very high. The management of state booty at Institution X has also been a finding by Audit Board of the Republic of Indonesia, which resulted in a Fair Opinion with an Exception.This study aimed to determine the implementation of asset management in the management of state booty in Institution X, using qualitative methods and case study approaches. The writing method used is descriptive analysis. This study indicates that asset management has been implemented in the management of state booty at Institution X, but there are still weaknesses in its implementation. These weaknesses are that the lack of the number and capacity of human resources to manage state booty, and the unavailability of an integrated information system from all units, and the weak monitoring system.